Hospitality in American Literature and Culture: Spaces, Bodies, Borders - More, Octavian (Studia Universitatis Babeș-Bolyai. Philologia, 2021)
ANA MARIA MANZANAS CALVO, JESÚS BENITO SÁNCHEZ (EDS.), HOSPITALITY IN AMERICAN LITERATURE AND CULTURE: SPACES, BODIES, BORDERS, ROUTLEDGE, 2017, 214 P.